Climate change and animal production - ?lvarez, Adri?n (Cuban Journal of Agricultural Science, 2014)
The terms greenhouse effect and climate change are frequently treated indistinctly by mass media, even though conceptually they make reference to totally different processes. While the first is a natural phenomenon, resulting from gas capturing by molecules present in the terrestrial atmosphere of the thermal energy reflected by the surface of the planet, that warms the planet in a similar way as it occurs in a greenhouse; the second is a process originated by the peculiarities inherent to the socio-economic systems and by their moving forces, which together determine the emission levels to the atmosphere of natural and artificial gases which are a consequence of the development, and that have the capacity of warming the atmosphere additionally to the greenhouse effect.